THE EFFECTIVENESS OF CONTEXT-BASED INDONESIAN MORPHOLOGY COURSE TEXTBOOKS FOR UNIVERSITY STUDENTS - Tri Astuti; Nur Nisai Muslihah (Jurnal Ilmiah Bina Bahasa, 2026)
Linguistic learning in higher education requires learning materials that are not only informative but also capable of deepening students’ conceptual understanding and encouraging active engagement in the learning process. This study investigates the effectiveness of a context-based textbook in enhancing students’ comprehension of morphology, particularly in the Indonesian Morphology course. The One-Group Pretest–Posttest Design was used, with questionnaires administered before and after the textbook evaluation; its effectiveness was subsequently analyzed using a t-test and N-gain analysis in SPSS. The participants consisted of third-semester students enrolled in the Indonesian Language and Literature Education Program at Universitas PGRI Silampari. The t-test produced a Sig. (2-tailed) value of 0.000, lower than the 0.05 significance threshold, which indicates a statistically significant improvement in learning outcomes. The N-gain score of 0.70 falls within the moderate category, showing that the textbook substantially improved student learning. Furthermore, student responses to the questionnaire averaged 88.58%, which was categorized as “convenient,” indicating a high level of acceptance of the learning material. In conclusion, the context-based Indonesian Morphology textbook has proven effective and practical for higher education. It not only enhances students’ conceptual understanding but also fulfills their needs for relevant and accessible learning resources.